2013
DOI: 10.1007/s11230-013-9417-8
|View full text |Cite
|
Sign up to set email alerts
|

New species of Kiluluma Skrjabin, 1916 (Nematoda: Strongylida) from the white rhinoceros Ceratotherium simium (Burchell), with a redescription of K. solitaria Thapar, 1924

Abstract: Three species of Kiluluma Skrjabin, 1916 were identified in Ceratotherium simium (Burchell) from a captive population in New South Wales, Australia, based on analysis of the second internal transcribed spacer (ITS-2) of ribosomal DNA. One species was identified as K. solitaria Thapar, 1924 and is redescribed. A second species is new and is described here as K. ceratotherii n. sp. The third species is new but was represented by two individuals only and is described but is not named.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…The species described here possesses a sinuous anterior margin to its buccal capsule, thereby immediately distinguishing it from all congeners other than K. solitaria Thapar, 1924, K. ceratotherii Beveridge & Jabbar, 2013 and Kiluluma sp. described but not named by Beveridge & Jabbar (2013). The current species differs from both K. solitaria and K. ceratotherii in that the tips of the leaf crown elements are exerted in these species but not in the species described here.…”
Section: Remarksmentioning
confidence: 61%
See 1 more Smart Citation
“…The species described here possesses a sinuous anterior margin to its buccal capsule, thereby immediately distinguishing it from all congeners other than K. solitaria Thapar, 1924, K. ceratotherii Beveridge & Jabbar, 2013 and Kiluluma sp. described but not named by Beveridge & Jabbar (2013). The current species differs from both K. solitaria and K. ceratotherii in that the tips of the leaf crown elements are exerted in these species but not in the species described here.…”
Section: Remarksmentioning
confidence: 61%
“…The genus Kiluluma Skrjabin, 1916, currently contains 14 species, comprising 12 species from African rhinoceroses, the black rhinoceros, Diceros bicornis (Linnaeus) and the white rhinoceros, Ceratotherium simum (Burchell) (Skrjabin, 1916;Thapar, 1924Thapar, , 1925Beveridge & Jabbar, 2013), with one species (K. vernayi Sandground, 1933) described from the Javan rhinoceros Rhinoceros sondaicus Desmarest by Sandground (1933) and another species K. longipene (Molin, 1861) from the South American tapir, Tapir terrestris (Linnaeus) (as T.…”
Section: Introductionmentioning
confidence: 99%
“…This is not always possible as Tan et al (2012) found no morphological differences in a geographically disjunct population of Macroponema comani. However, such molecular studies are increasingly significant in the delineation of species of strongyloid nematodes (Chilton et al, 2012, Beveridge andJabbar 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The most outstanding example and the strongylid parasites of the large intestine of equids, with 19 genera and 64 species belonging to the family Strongylidae currently described (Lichtenfels et al 2008). Similarly complex associations occur in the large intestines of elephants and rhinoceroses (four genera and 49 species belonging to the strongyloid tribes Quiloninea, Kiluluminea and Murshidiinea) (Chabaud 1957, Round 1968, Beveridge and Jabbar 2013 as well as in tortoises (Lichtenfels and Stewart 1981), although the latter communities have been less well documented.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of equids (horses, donkeys and zebras), 14 genera and 50 species of strongyloid nematodes belonging to the tribe Cyathostominea are currently recognized (Lichtenfels et al 2008), with the common co-occurrence of many species (Bucknell et al 1996; Anjos and Rodrigues, 2003; Bu et al 2009; Kuzmina et al 2009), but again with differences in the distribution of species within the gastro-intestinal tract (Ogbourne, 1976; Mfitilodze and Hutchinson, 1985; Bucknell et al 1995; Stancampiano et al 2010). Comparably detailed studies on the strongyloid nematodes of elephants and rhinoceroces have not been conducted, but four genera and 49 species belonging to the related strongyloid tribes Kiluluminea, Murshidinea and Quiloninea are known to occur in their large intestines (Chabaud, 1957; Round, 1968; Canaris and Gardner, 2003; Beveridge and Jabbar, 2013). In the case of kangaroos and wallabies (family Macropodidae) some 36 genera and 256 species of nematodes belonging to the sub-family Cloacininae occur in the sacculated forestomach (Beveridge and Chilton, 2001), frequently in large numbers (Beveridge and Arundel, 1979), with again, some degree of spatial separation within the stomach (Mykytowycz, 1964; Arundel et al 1979; Pamment et al 1994).…”
Section: Introductionmentioning
confidence: 99%